Education And Education of The Young Generation in The XXI Century - Rahimova Mavlyuda Nabijanovna (Genius Journals, 2022)
This article provides information on "Education and upbringing of the younger generation in the XXI century" and the individual approach and attitude to each child in the educational process.
Keywords: Students; education; upbringing; lessons